2018
DOI: 10.2478/aiht-2018-69-3065
|View full text |Cite
|
Sign up to set email alerts
|

Role of gene polymorphisms in vitamin D metabolism and in multiple sclerosis

Abstract: Multiple sclerosis (MS) is a complex inflammatory disease of the central nervous system (CNS) resulting in neurological impairment and disability. There is evidence that adequate vitamin D levels may lower the risk of MS development. The aetiology of MS is complex and involves both genetic and environmental factors. In fact, not one but several genes are believed to lead to the disease. As for environmental factors, one of the most important risk factors is vitamin D deficiency, which, in turn, is closely rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 41 publications
1
4
0
Order By: Relevance
“…Moreover, our genetic models' analysis results showed a significant association under three models (dominant, recessive, and codominant) OR > 1, the strongest impact was for homozygous codominant which may emphasize the potential role of GG genotypes as a risk factor for developing MS. These findings come in agreement with previous studies which showed that a decrease in the concentration of vitamin D in patients with MS was associated with the presence of genetic changes, most notably at rs7041 in the DBP gene [16,33] and can be explained that genetic polymorphisms cause low concentration of vitamin D levels and increase susceptibility to develop MS [34][35][36].…”
Section: Discussionsupporting
confidence: 93%
“…Moreover, our genetic models' analysis results showed a significant association under three models (dominant, recessive, and codominant) OR > 1, the strongest impact was for homozygous codominant which may emphasize the potential role of GG genotypes as a risk factor for developing MS. These findings come in agreement with previous studies which showed that a decrease in the concentration of vitamin D in patients with MS was associated with the presence of genetic changes, most notably at rs7041 in the DBP gene [16,33] and can be explained that genetic polymorphisms cause low concentration of vitamin D levels and increase susceptibility to develop MS [34][35][36].…”
Section: Discussionsupporting
confidence: 93%
“…Growing evidence suggests that vitamin D is an environmental factor significantly affecting MS prevalence that is closely associated with the latitudinal gradient, where an increased exposure to UVB stimulates the cutaneous production of vitamin D reducing the risk of disease [71,72]. Accordingly, low levels of 25(OH)D, in association with the presence of genetic polymorphisms involving the metabolism of vitamin D, imply a greater risk of developing MS [73][74][75]. In addition, it has been observed that the presence of gene variants of the CYP27B1 seems to increase the risk and activity of MS [76][77][78].…”
Section: Multiple Sclerosismentioning
confidence: 99%
“…Additionally, vitamin D can modulate both adaptive and innate immunity [ 191 ]. Indeed, vitamin D deficiency is associated with several autoimmune diseases [ 192 ], for example, rheumatoid arthritis (RA) [ 193 , 194 ], inflammatory bowel disease (IBD) [ 195 , 196 , 197 , 198 ] and multiple sclerosis (MS) [ 199 , 200 , 201 , 202 ]. Associations between low vitamin D status and autoimmune thyroid diseases and thyroid cancer were also found [ 203 ].…”
Section: Vitamin D: State Of the Artmentioning
confidence: 99%